The Role of Visual Media in the Mastery of Arabic Vocabulary (Mufradat) for Grade VII Students of Salafiyah Wustho Islamic Centre Bin Baz Yogyakarta - Ayatullah Muhaimin; Grean Thoms (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research is based on initial observations showing that Grade VII students at Salafiyah Wustho Islamic Center Bin Baz Yogyakarta have more outstanding academic achievements compared to other classes. The purpose of this study is to understand the role of image media in mastering Arabic vocabulary (mufrodat) in Grade VII A, as well as to identify the factors of success and obstacles in learning the vocabulary. The research uses a qualitative approach with data collection methods such as observation, interviews, and documentation, with data analysis conducted qualitatively. Data validation is carried out through triangulation of sources and methods. The results of the study show that the use of image media in Arabic language learning, especially for mufrodat, has significant advantages and benefits. Image media contributes positively to visual understanding, memory retention, learning interest, and communication skills in Arabic. However, there are challenges in its use, especially in illustrating abstract or complex vocabulary. Therefore, selecting and adjusting images appropriately to the students' level of understanding is crucial to maximize the benefits of image media in learning. These findings emphasize the importance of integrating image media into language learning methods, particularly in Islamic educational environments such as Islamic boarding schools.